An Integrated Framework of Critical Techniques in Implementation of Total Quality Management - Amir, Azizi (IEEE, 2015)
In order to survive in a competitive market, organizations have to continuously improve the quality and productivity of the products and processes. An integrated framework is the valuable approach for achieving this goal. In this study, the critical techniques in hard Total Quality Management (TQM) are highlighted first. Then the possibility of designing an integrated framework was investigated, which enables to present the interrelationship between the critical techniques and the priority of effectiveness degree of each technique in successful implementation of TQM in automotive industry as a benchmarking model. The modern quality paradigms emphasize the importance of customer satisfaction as a driver to the improvement process. This study also focused on customer satisfaction approach by six critical factors. In this paper, we carried out an empirical study in order to verify the importance of effectiveness of the critical techniques for TQM implementation improvement and their effect upon TQM results. The integrated framework is proposed using extracting knowledge and experience from industrial and academic who were in charge of quality in 120 ISO-certified Malaysian automotive firms. The results show the arrangement sequence of the TQM critical techniques to achieve a better overall performance of the Automotive manufacturing industry using the analytical hierarchy process pair-wise comparison.